2016
DOI: 10.1002/ana.24630
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging reveals rapid astrocyte depletion and axon damage in a model of neuromyelitis optica‐related pathology

Abstract: ObjectiveNeuromyelitis optica (NMO) is an autoimmune disease of the central nervous system, which resembles multiple sclerosis (MS). NMO differs from MS, however, in the distribution and histology of neuroinflammatory lesions and shows a more aggressive clinical course. Moreover, the majority of NMO patients carry immunoglobulin G autoantibodies against aquaporin‐4 (AQP4), an astrocytic water channel. Antibodies against AQP4 can damage astrocytes by complement, but NMO histopathology also shows demyelination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
3
30
0
Order By: Relevance
“…Damage of astrocytes with axonal degeneration was dependent on titre of AQP4 antibody and complement. Data from this experimental rodent model using in vivo imaging96 are consistent with the patterns of neurodegeneration described in human NMO pathology79 (figure 3). …”
Section: Neurodegeneration In Nmosupporting
confidence: 77%
See 2 more Smart Citations
“…Damage of astrocytes with axonal degeneration was dependent on titre of AQP4 antibody and complement. Data from this experimental rodent model using in vivo imaging96 are consistent with the patterns of neurodegeneration described in human NMO pathology79 (figure 3). …”
Section: Neurodegeneration In Nmosupporting
confidence: 77%
“…RNFL thinning and loss of ganglion cells in the presence of AQP4 + astrocytes indicate secondary retrograde degeneration after optic neuritis 79. Furthermore, in vivo imaging of the spinal cord to study the formation of experimental NMO-related lesions caused by human AQP4 antibody in mice demonstrated that human AQP4 antibody results in acute depletion of astrocytes with initial oligodendrocyte survival 96. This was followed after 2 hours of antibody application by secondary axonal injury 96.…”
Section: Neurodegeneration In Nmomentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, simulations with convolutional neural networks that incorporate biophysically plausible neural malfunctions may provide a window of opportunity to better diagnose, for instance, confusion in visual image classification. Focal axonal swelling pathologies are present in AD [2,17,53,91] and in other neurodegenerative diseases such as Parkinson's disease [86,60,28], Multiple Sclerosis [26,70,90], and others [36,50,55,56]. In many cases, FAS arise by the agglomeration of specific proteins over time [16,68], and again, the computational modeling of focal axonal swellings and their effects to spike propagation from [63] provide a platform to investigate network dysfunction.…”
Section: Aging and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Recently, Herwerth et al (53) used intravital imaging to monitor the early phases of CNS lesion formation following the application of AQP4-IgG and HC to murine spinal cord in situ. Although oligodendrocytes remained relatively intact soon after the onset of astrocyte destruction, progressive axonal swellings were prominent (Fig.…”
Section: Nmo Lesion Pathology: Linking Astrocyte Destruction To Demyementioning
confidence: 99%